2018
DOI: 10.1063/1.5029363
|View full text |Cite
|
Sign up to set email alerts
|

Broadband voltage rectifier induced by linear bias dependence in CoFeB/MgO magnetic tunnel junctions

Abstract: In this paper the perpendicular magnetic anisotropy (PMA) is tailored by changing the thickness of the free layer with the objective of producing MTJ nano-pillars with smooth linear resistance dependence with both in-plane magnetic field and DC bias. We furthermore demonstrate how this linear bias dependence can be used to create a zero-threshold broadband voltage rectifier, a feature which is important for rectification in wireless charging and energy harvesting applications. By carefully balancing the amount… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The free layer is composed of Co 20 Fe 60 B 20 while the MgO tunnel barrier ensures a high magnetoresistance effect [23,24]. The perpendicular magnetic anisotropy (PMA) in the Co 20 Fe 60 B 20 -MgO bilayer is caused by an interfacial effect that arises from the hybridization between the O (from the MgO) and Fe (from the Co 20 Fe 60 B 20 ) orbitals, and can be controlled by the Co 20 Fe 60 B 20 composition and thickness of the free layer [13,14,25,26]. In other words, below a critical thickness, the free layer easy axis is outof-plane.…”
Section: B Device Realization and Characterizationmentioning
confidence: 99%
“…The free layer is composed of Co 20 Fe 60 B 20 while the MgO tunnel barrier ensures a high magnetoresistance effect [23,24]. The perpendicular magnetic anisotropy (PMA) in the Co 20 Fe 60 B 20 -MgO bilayer is caused by an interfacial effect that arises from the hybridization between the O (from the MgO) and Fe (from the Co 20 Fe 60 B 20 ) orbitals, and can be controlled by the Co 20 Fe 60 B 20 composition and thickness of the free layer [13,14,25,26]. In other words, below a critical thickness, the free layer easy axis is outof-plane.…”
Section: B Device Realization and Characterizationmentioning
confidence: 99%
“…Later, broadband STD rectification was demonstrated experimentally [ 61,62 ] for zero DC bias (see example in Figure 7). In the work by Fang et al., [ 61 ] a nonlinear regime broadband detection of STD was demonstrated and compared with the low‐power Schottky diode.…”
Section: Broadband Std Rectification Modementioning
confidence: 99%
“…It was shown that the considered STD maintains high enough DC voltage to supply the real low power nanodevice (black phosphorus photosensor). In the work by Tarequzzaman et al., [ 62 ] MTJs with a smooth linear resistance dependence on DC bias and in‐plane external magnetic field were produced. Such a dependence was obtained by changing the thickness of the free layer, which allows to manipulate by perpendicular magnetic anisotropy (PMA).…”
Section: Broadband Std Rectification Modementioning
confidence: 99%
“…Figure 2.10a presents a schematic of the measurement setup in which a DC current was sent through a bias tee. An external RF signal at 80 MHz was added to the DC current using a microwave circulator (4)(5)(6)(7)(8)(9)(10)(11)(12). An SHNO with a 200 nm constriction is shown in the inset to Fig.…”
Section: Current Modulation Of Spin Hall Nano Oscillatormentioning
confidence: 99%
“…It also holds great promise even for the realization of universal memory [5][6][7]. Extensive research by the spintronics community has aimed at achieving nanoscale spin-based microwave components, such as microwave generators [8][9][10][11], rectifiers [12], spin diodes [13], spin-wave generators [14,15], and modulators [16][17][18][19][20][21][22][23], which could be used as building blocks of communication systems.…”
Section: Introductionmentioning
confidence: 99%